Molecular-Based Diversity Studies and Field Surveys Are Not Mutually Exclusive: On the Importance of Integrated Methodologies in Mycological Research - Cazabonne, Jonathan; Bartrop, Lachlan; Dierickx, Glen; Gafforov, Yusufjon; Hofmann, Tina A.; Martin, Thomas E.; Piepenbring, Meike; Rivas-Ferreiro, Mauro; Haelewaters, Danny (Frontiers in Fungal Biology, 2022)
Understanding and describing the diversity of living organisms is a great challenge. Fungi have for a long time been, and unfortunately still are, underestimated when it comes to taxonomic research. The foundations were laid by the first mycologists through field observations. These important fundamental works have been and remain vital reference works. Nevertheless, a non-negligible part of the studied funga escaped their attention. Thanks to modern developments in molecular techniques, the study of fungal diversity has been revolutionized in terms of tools and knowledge. Despite a number of disadvantages inherent to these techniques, traditional field-based inventory work has been increasingly superseded and neglected. This perspective aims to demonstrate the central importance of field-based research in fungal diversity studies, and encourages researchers not to be blinded by the sole use of molecular methods.